Spital als Lebensform, Band 2 Österreichische Spitalordnungen und Spitalinstruktionen der Neuzeit - Scheutz, Martin (2015)
The voluminous publication edits 203 such items covering all of the Austrian territories from the Late Middle Ages to the 19th century. Hospital rules, instructions for hospital staff, job descriptions, special rules as, for example, prayer orders and dietaries, but also inventories were meant to channel the way of life of inmates and staff. Each of the edited sources is accompanied by a survey on the history of the hospital and a comment contextualising the contents, which necessitated pioneering archival research in many cases where no serious scholarly treatment of the hospitals' history was available. First volume: http://e-book.fwf.ac.at/o:799